2010
DOI: 10.1038/onc.2010.201
|View full text |Cite
|
Sign up to set email alerts
|

miR-200bc/429 cluster targets PLCγ1 and differentially regulates proliferation and EGF-driven invasion than miR-200a/141 in breast cancer

Abstract: The genes encoding microRNAs of the human miR-200 family map to fragile chromosomal regions and are frequently downregulated upon tumor progression. Although having been reported to regulate epithelial-tomesenchymal transition and transforming growth factorbeta-driven cell invasion, the role of the miR-200 family in EGF-driven breast cancer cell invasion, viability, apoptosis and cell cycle progression is still unknown. In particular, there is no study comparing the roles of the two clusters of this miRNA fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(148 citation statements)
references
References 32 publications
7
138
0
3
Order By: Relevance
“…Recent progress in cancer biology has revealed that miRNAs are frequently deregulated in various human cancers, including breast cancer. For instance, elevated miR-21 expression has been reported in breast tumors (Volinia et al, 2006), while miR-335 and miR-200c have been shown to inhibit metastatic cell invasion (Tavazoie et al, 2008;Uhlmann et al, 2010). These findings demonstrate the ability of miRNAs to modulate the development of malignancies by regulating critical cancer-related genes and signaling pathways.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent progress in cancer biology has revealed that miRNAs are frequently deregulated in various human cancers, including breast cancer. For instance, elevated miR-21 expression has been reported in breast tumors (Volinia et al, 2006), while miR-335 and miR-200c have been shown to inhibit metastatic cell invasion (Tavazoie et al, 2008;Uhlmann et al, 2010). These findings demonstrate the ability of miRNAs to modulate the development of malignancies by regulating critical cancer-related genes and signaling pathways.…”
Section: Introductionmentioning
confidence: 84%
“…miR-520/373 family modulates NF-jB and TGF-b signaling I Keklikoglou et al cancer cells in vivo, a chorioallantoic membrane (CAM) assay was performed (Zijlstra et al, 2002;van der Horst et al, 2004). MDA-MB-231 cells were transfected with miR-520/373 family mimics or with small interfering RNAs targeting RELA and TGFBR2 genes and were inoculated on the upper CAM of 10-day-old chicken embryos.…”
Section: Resultsmentioning
confidence: 99%
“…25 MiR-200c inhibits matrix invasion by breast cancer cell MDA-MB-231, 26 while miR-200b/c/429 cluster significantly reduces cell growth and promotes apoptosis. 27 Meanwhile, miR-200 family also inhibits EMT by downregulating ZEB1 and ZEB2. [28][29][30] These studies all suggest anti-cancer roles of miR-200 family.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-200 family has been found to play a critical role in the maintenance of the epithelial phenotype by targeting ZEB1, SIP1, and SIRT1, thus preventing the silencing of E-cadherin (30,31). Within the miR-200 family, there are two clusters: miR-200b/200a/429 located on chromosome 1p36, and miR-200c/141 located on chromosome 12p13 (32).…”
mentioning
confidence: 99%